PENGARUH BUDAYA ORGANISASI DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING - Yanti Mayasari Ginting; Sherly Sherly; Fransiska Natalia Ralahallo; Yupiter Mendrofa; Nandang Bekti Karnowati (Manis: Jurnal Manajemen dan Bisnis, 2022)
The results of this study indicate that (1) Organizational culture has a positive and significant effect on employee performance (2) work involvement has a positive and significant effect on organizational commitment (3) Organizational culture has a positive and significant effect on employye performance (4) Work involvement has no effect on employye performance (5) Organizational commitment has a positive and significant effect on performance (6) Organizational commitment mediates the relationship between organizational culture and employye performance (7) Organizational commitment mediates the relationship between job involvement and employee performance